Photodetection and scintillation characterizations of novel lead-bismuth double perovskite halides. Issue 31 (15th July 2022) - Maddalena, Francesco; Witkowski, Marcin E.; Makowski, Michal; Bachiri, Abdellah; Arramel,; Yang, Ting; Mahyuddin, Muhammad Haris; Baravaglio, Matilde; Boutchich, Mohamed; Drozdowski, Winicjusz; Dujardin, Christophe; Birowosuto, Muhammad Danang; et al.
Abstract : Double perovskite materials with large effective atomic numbers and high mass densities generate short absorption length for radiation detection. Bromide and iodide variants were characterized for their scintillation and photodetection properties. Abstract : Double perovskites are materials exhibiting excellent properties for a variety of optical and electrical applications. In this paper, we characterize the structural, electronic, optical, electrical and scintillation properties of two variants of lead-bismuth halide double perovskite, with the general chemical composition of Cs4 PbBi2 X12 (X = Br, I). Density functional theory calculations reveal that the Br- and I-variants have direct and indirect bandgaps, respectively. The Cs4 PbBi2 X12 perovskites also show a broad emission down to near infrared, suggesting the presence of self trapped excitons. Photoluminescence time-resolved measurements show a very fast decay time with average decay times of 4.1 ns and 0.39 ns, for the Br- and I-variant, respectively. Photodetectors fabricated with the Cs4 PbBi2 X12 perovskites show clear rectification under bias, and a moderate response to illumination. Due to the presence of very heavy atoms and density of the material, the Cs4 PbBi2 X12 perovskites are strong X-ray absorbers with attenuation lengths comparable to Gd2 O2 S, a standard X-ray phosphor. The Cs4 PbBi2 X12 perovskites also show strong scintillation at cryogenic temperatures below 30 K, but thermal quenching severely reduces the light yield at room temperature. Although the performances of both crystals for photodetectors and scintillators are still low in comparison with some other perovskites, they are still a very promising materials due to their short absorption length and high theoretical maximum light yield, and their optoelectronic properties could be significantly improved by ion doping.